Urgensi Literasi Media Terhadap Pola Pikir Masyarakat - Dian Risdiawati (IAIN Madura, 2020)
This discussion is focused on two main things, namely related to media literacy and community mindset. In this context, the media is a means that has the potential to produce and disseminate social meaning, or in other words, the media plays a major role in determining the meaning of events that occur in the world for a particular culture, society, or social group. However, often the public quickly condemns media performance or identifies improperness and declares detrimental effects. It is rare for people to question their role in mass communication. Thus, media literacy is important to be developed in society to increase the ability of media literacy. Understanding media literacy is very important to be understood by the community because with an adequate understanding of it will create a society that can think critically and have a healthy mindset. The public is expected to be able to control the impact of media shows, no longer be controlled from the impressions presented by the media so that it can give birth to a generation of media literacy. Society can determine the direction of its mind and is no longer influenced by one perspective formed by the media.